Сыщик Алиса: повесть-сказка / Кир Булычев ; худож. Е. Т. Мигунов - Булычев Кир (Детям, 2000)
5-7кл Экземпляры: ДБ (2000) / Инвентарный номер: 33146 / Цена: 32.50 / Авт.знак: Б 90 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6